Extraction of Copper(II) with Salicylideneaniline from Sulphate and Perchlorate Media - Barkat, D.; Omari, M. (Asian Journal of Chemistry, 2016)
The liquid-liquid extraction of copper(II) from sulphate and perchlorate media by salicylideneaniline (HSA) in chloroform is studied. The ionic strength effect of the aqueous phase shows that the extraction of copper(II) increases with decreasing concentration of sulphate. At initially 10–4 m in the aqueous phase, Cu(II) is extracted as the complex Cu(SA)2·HSA. Sulphate complex of Cu(II) is formed in the aqueous phase. The copper-sulphate interaction has been made in evidence by using the Debye-Hückel extracted limiting law of ionic activity coefficient.